Progress on the role of exosomal miRNAs in organ fibrosis - FANG Lu, LIU Ruiqi, LIANG Peng, CEN Ying (Jichu yixue yu linchuang, 2023)
Exosomes are tiny vesicles that are actively secreted by a variety of cells, which regulate various physiological and pathological processes of the body by carrying proteins, lipids, miRNAs and other biological molecules. Exocrine microRNAs(miRNAs) stably exist in the body fluid circulation and participate in many pathological processes of organs. In organ fibrosis disease, the content of the exosomal miRNAs shows significant differential expression profile as compared with normal tissues, and promotes or inhibits organ fibrosis by regulating different signal pathways. It is considered to be the latest biological indicator for diagnosing organ fibrosis and judging its degree of fibrosis, and a new therapeutic target for fibrosis disease.